Dear Evan Hansen - Pasek, Benj; Paul, Justin, 1985- (Hal Leonard, 2017)
Song lists: -- Anybody have a map -- Waving through a window -- For Forever -- Sincerelyn me -- Requiem -- If i could tell her -- Disappear -- You will be found -- To break in a glove -- Only us -- Good for you -- Words fail -- So big/so small.